Cobalt Oxide–Tin Core–Shell Nanowire Arrays as High‐Performance Electrodes for Lithium‐Ion Batteries. Issue 11 (3rd August 2016) - Wu, Man; Du, Ning; Wu, Hao; Liu, Wei; Chen, Yifan; Zhao, Wenjia; Yang, Deren
Abstract: Both cobalt oxide and tin are electrochemically active materials, and can be integrated into hybrid core–shell nanowire structures that can participate in lithium‐ion insertion‐deinsertion process. We demonstrate the synthesis of cobalt oxide–tin (Co3 O4 –Sn) core–shell nanowire arrays by the hydrothermal synthesis of Co3 O4 nanowire arrays and subsequent deposition of the tin layer via a RF‐sputtering method. When used as anode materials in lithium‐ion batteries, the Co3 O4 –Sn core–shell nanowire electrodes show better cyclability and enhanced rate capacities compared to bare Co3 O4 electrodes. The improved performance can be attributed to the introduction of the tin layer, which improves the electrical conductivity and structural stability of the Co3 O4 nanowire arrays. Abstract : Looking to get arrays : Arrays of cobalt oxide (Co3 O4 ) nanowire on a titanium substrate are synthesized by a hydrothermal process and subsequent annealing approach. A layer of tin is deposited onto the Co3 O4 nanowire arrays by direct RF‐sputtering. When used as anode materials in lithium‐ion batteries, the Co3 O4 –Sn core–shell nanowire electrodes show better cyclability and enhanced rate capacities compared to bare Co3 O4 electrodes.